The Effect of the Covid-19 Pandemic on Mental Health: Quasi-Experimental Evidence from Indonesia - Sahadewo, Gumilang; Hendra Permana, Yudistira; Gu, Yuanyuan; Schroeder, Elizabeth-Ann (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: This research aims to explore and analyze the effect of the COVID-19 pandemic on mental health status as measured by DASS-21. Background Problems: The prolonged impact of the COVID-19 pandemic on the global economy may have adversely affected mental health. A decrease in income and consumption and the uncertainties surrounding job security and business performance have been some of the main factors contributing to mental health issues. Novelty: This paper aims to evaluate the effect of the COVID-19 pandemic—as a natural experiment—on mental health measured by DASS-21 and how the effect of the pandemic varied across different socioeconomic subgroups. Research Methods: We conducted an online survey across Indonesia to collect self-reported mental health status and socioeconomic characteristics before and during the COVID-19 pandemic to measure its impacts on mental health. Finding/Results: Our results suggest that the COVID-19 pandemic has had an adverse impact on mental health, particularly in terms of anxiety and stress. The effect has been higher among individuals with lower self-efficacy, lower expenditure, and lower education levels. Conclusion: The health and economic crisis driven by the COVID-19 pandemic affected individuals' mental health, suggesting the need for appropriate policy responses.